Social Inclusion and Levels of Urbanisation: Does It Matter Where You Live? - Adele Whelan; Anne Devlin; Seamus McGuinness (Institute of Labor Economics (IZA), 2023)
Are individuals living in distinct urban or rural settings more likely to experience barriers to social inclusion? If so, what are the nature of the barriers that they face? Using a unique administrative dataset for Ireland's dominant social inclusion programme, this paper examines the effect of location on the incidence of barriers to social inclusion. We find that some forms of social exclusion, particularly those which are related to economic exclusion, are more prevalent for those in independent urban towns compared to cities, commuter towns or rural areas, even after controlling for area-level deprivation. The results suggest that existing policy, which has traditionally focused on tackling social disadvantage in the most urban or rural areas, is not well targeted and would benefit from having a wider spatial focus.
Keywords: R10; R58; P25; J15; 330; social inclusion; urban disadvantage; community economic development; jobless household; lone parents; disability; homelessness; ethnic minority